Reversible intercalation of methyl viologen as a dicationic charge carrier in aqueous batteries - Zhixuan Wei (Nature Portfolio, 2019)
Rechargeable batteries are governed by reversible intercalation reactions. Here the authors expand the intercalation chemistry to include methyl viologen as a large dicationic charge carrier in aqueous batteries. The bonding between guest and aromatic host is not pure ionic but shows strong covalent character.